Aplikasi Laporan Keuangan Musala Al-Maghfiroh RW 023 Kelurahan Kaliabang Tengah Bekasi Berbasis Website - Untung Surapati; Tino Saputra; Tamzis; Muhammad Syani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The prayer room is a place of worship and is one of the centers of Muslim activities apart from the mosque. The financial management of prayer rooms which still uses a manual management system causes prayer rooms to have difficulty processing data and takes a long time. Therefore, a prayer room financial management information system is needed to make it easier for managers to input data and increase data accountability and transparency. This research aims to develop a web-based prayer room financial management information system. The data collection methods used were observation and literature study. System development is carried out through needs analysis, basic data design, and interface design using UML. The system was built using the PHP and HTML programming languages, using a bootstrap framework and creating basic data using MySQL. The research results show that the web-based prayer room financial management information system can make it easier for managers to input prayer room asset and financial data. This system can also increase accountability and data transparency, so that it can provide real-time financial report information to the congregation and the public regarding prayer room management. It is hoped that this research can make a positive contribution to the efficiency of prayer room financial management, become a reference for other prayer rooms that still use manual systems, and overall, strengthen the quality of community service activities at the local level.